Endovascular Repair of an Inflammatory Abdominal Aortic Aneurysm Combined with a Congenital Pelvic Kidney: Case Report and Literature Review - Papadoulas, Spyros; Kouri, Natasa; Tsimpoukis, Andreas; Zampakis, Petros; Papasotiriou, Marios; Moulakakis, Konstantinos G.; Kakkos, Stavros K. (AORTA, 2022)
The coexistence of an abdominal aortic aneurysm and a congenital pelvic kidney is extremely rare. We present a 66-year-old male with an inflammatory aneurysm and an aberrant origin of the superior mesenteric artery. The inflammatory infrarenal abdominal aortic aneurysm with a congenital left pelvic kidney was successfully treated with endovascular repair. Coverage of one out of the two renal ectopic arteries was performed, without clinical evidence of renal function impairment.
Keywords: inflammatory; abdominal aortic aneurysm; congenital pelvic kidney; endovascular aneurysm repair